Bibliometric Analysis of Cybersecurity and Risk Management in Accounting - Loso Judijanto (West Science Interdisciplinary Studies, 2025)
This study performs a thorough bibliometric analysis to investigate the intellectual landscape and thematic evolution of cybersecurity and risk management research in the field of accounting.  The study used Scopus-indexed articles and visual analytics produced via VOSviewer and Bibliometrix to delineate keyword co-occurrences, author collaborations, institutional networks, and contributions by countries.  The findings indicate that cybersecurity, risk management, and risk assessment constitute the conceptual foundation of the discipline, acting as fundamental elements that link diverse related subjects such as network security, information management, cloud computing, blockchain, and data privacy.  Temporal overlay analysis reveals a transition from an initial focus on technical vulnerabilities and fundamental risk assessment to a contemporary emphasis on digitalization, accounting system security, and developing technologies.  Co-authorship and institutional networks exhibit fragmented yet expanding collaboration patterns, with the United States serving as the principal worldwide center.  This study enhances the literature by delineating predominant topics, upcoming research frontiers, and collaboration deficiencies, so establishing a systematic basis for future investigations.  These insights assist scholars and practitioners in formulating more cohesive, robust, and proactive cybersecurity measures inside accounting frameworks.